Transatlantic Literary Studies - Manning, Susan (Edinburgh University Press, 2007)
The first volume of critical texts to define the field of Transatlantic Literary Studies. The Reader provides 42 exemplary readings that map the theoretical and literary aspects of this growing cross-disciplinary subject area.